A pesquisa histórica sobre a educação no período da ditadura cívico-militar - Galak, Eduardo Lautaro; Sá, Elizabeth Figueiredo; de Souza Chaloba, Rosa Fátima [UNESP] (Universidade Estadual de Maringa, 2025)
Education was one of the sectors most impacted by the authoritarian regime instituted in 1964 in Brazil, not only by the violence, repression and truculence directed at students and teachers, but also by the uses that the military governments made of educational institutions and school culture as an instrument of control and ideological indoctrination, in addition to the profound transformations that they imprinted on the structure of the education system with the 1968 university reform (Law No. 5.540/68) and the reform of primary and secondary education (Law No. 5.692/71), whose implications we still experience today. The panorama is similar, but not the same, in other Latin American countries, a product of the Condor Plan, which disseminated government techniques on populations in political, economic and pedagogical terms. In recent years, a growing number of researchers have focused on the study of the history of education in the period of civic-military dictatorships, interrogating this historical period with new questions and from different approaches. Undoubtedly, the renewal of the field of History and History of Education has contributed enormously to the broadening of the researchers' questionnaire. The expansion of research sources, the relationship of history with other fields of knowledge such as Anthropology, Psychology, Linguistics, the look at culture and notions of practices and representations have enriched a multiplicity of themes and interpretations (Barros, 2011). But the study of the dictatorship period has difficulties, as it dialogues with the current political debate and is immersed in disputes over memory.[1] In addition, it is involved in controversies of a theoretical nature in the disciplinary fields themselves. The purpose of this dossier, now published by the Revista Brasileira de História da Educação (Brazilian Journal of History of Education), is precisely to deepen knowledge on the subject and to open the way to the debate by questioning different analyzes about this historical period and its implications for education.